Atmospheric Aerosol Over Ukraine Region: Current Status of Knowledge and Research Efforts - Milinevsky, Gennadi; Danylevsky, Vassyl (Frontiers in Environmental Science, 2018)
In this paper the current status of knowledge and research efforts on atmospheric aerosol investigation over Ukraine region are reviewed. Several earlier results of atmospheric extinction, aerosol content and properties studies performed in Ukraine during the second part of 20 century are discussed. The recent findings on aerosol optical depth, Ångström exponent, optical and microphysical properties of aerosol particles (single-scattering albedo, size distribution, complex refractive index) and their seasonal variability obtained from both AERONET and portable sun-photometers measurements during the 2008–2016 period are presented and analyzed. Data of POLDER/PARASOL satellite instrument were also involved to study the aerosol properties over Ukraine and neighbor countries. The results showed that aerosol content and properties over Ukraine are very similar to ones over rest European urban regions but considerably lower than over polluted China territories. The first lidar measurements and the air quality evaluations by the PM concentration measurements in Ukraine are also discussed. The aerosol sources in Ukraine and surrounding territories are considered from analysis of the air mass back trajectory and simulation by GEOS-Chem model. The future satellite project Aerosol-UA for global aerosol studies by measurements of the scattered solar radiation polarization is discussed in the article.